DEALING WITH CHANGE: COMPONENTS VERSUS SERVICES. - Elfatatry, Ahmed (Communications of the ACM, 2007)
The article discusses changes in software design, focusing on the philosophy behind components and services. Businesses must deal with change on a constant basis, especially concerning the introduction of new technologies. Programmers often view change as an evil that should be avoided at every possibility, rather than an opportunity that can be embraced to make the design and behavior better. The author examines the ways in which change can be helpful for computer programmers and the software industry.